Utilising angle-dependent critical current data in the electromagnetic modelling of HTS coils. (6th January 2022) - Wimbush, Stuart C; Strickland, Nicholas M
Abstract: A detailed methodology is presented for modelling the electromagnetic characteristics of HTS coils using angle-dependent critical current data obtained from experimental measurements of real wire samples. The results of such an analysis are contrasted with those obtained using more prevalent approaches such as a global minimum critical current method or an elliptical field magnitude-dependent functional approximation. Several interesting design consequences of significance to real-world devices that emerge only when the full anisotropy of real wires is taken into account are outlined and discussed. These include the beneficial impact on various performance metrics of the adoption of mixed conductor windings, the importance of coil orientation in optimising device performance, and the potential opportunity to derive a specific design benefit from the targeted use of conductors possessing inclined planarity.